A novel shell-and-tube thermal energy storage tank: Modeling and investigations of thermal performance. (August 2019) - Mao, Qianjun; Liu, Ning; Peng, Li; Liu, Donghua
Highlights: A novel truncated cone shell-and-tube TES model has been designed. The melting process of a novel truncated cone tank has been investigated. An optimal truncated cone TES model has been obtained. Abstract: Utilizing the solar energy by thermal energy storage (TES) system is an important way to solve energy shortage and environmental pollution. In this paper, the air and nitrate salt have been selected as the heat transfer fluid (HTF) and phase change material (PCM), respectively, and the aim is to investigate the heat transfer performance of the storage tank. According to analyze the disadvantages of traditional cylindrical shell-and-tube TES tank, a novel truncated cone shell-and-tube TES tank has been established, and a new parameter namely Taper has been proposed. Meanwhile, the melting process of the TES tanks have been investigated by FLUENT software, and then the optimal TES tank with a Taper of 0.2072 has been obtained by comparing with the melting process of the four kinds of the truncated cone model. This research will provide theoretical guidance for future designing optimization of TES system for concentrated solar power (CSP) pant.